Socio-Religious Activities of Christian and Muslim Youth Organisations in Promoting Inter Religious Relations in Selected Universities in Kwara, Ogun and Oyo States, Nigeria (2015)
Socio-religious (S-R) activities, which are apparent in Christian and Muslim youth organisations, are an integral part of their convenance. Previous studies on S-R activities have dwelt on their contributions to the growth of Christian and Muslim communities with little attention to their relevance in enhancing inter-religious relations in Nigerian universities. This study, therefore, examined scriptural studies, outreaches, social and educational activities of Christian and Muslim youth organisations in selected universities in Kwara, Ogun and Oyo states, Nigeria, with a view to identifying how they promote inter-religious relations. This study is premised on Hans Kung‟s theory of interaction of religions. One thousand two hundred copies of a questionnaire were purposively administered in equal proportion to leaders and members of Unilorin Christian Union (UCU), Ogun Varsity Christian Fellowship (OVCF), Ibadan Varsity Christian Union (IVCU) and Muslim Students‟ Society of Nigeria (MSSN) in Olabisi Onabanjo University (OOU), University of Ibadan (UI) and University of Ilorin (Unilorin). In-depth interviews were conducted with randomly selected 45 Christians and 45 Muslims: 14 advisers, 26 leaders and 50 members of the organisations. Data were subjected to descriptive and thematic analyses. Four S-R activities common to the six organisations identified were: scriptural studies, outreaches, social and educational programmes. Eighty Five percent of the respondents noted that scriptural studies on religious teachings and right conduct enlighten them on religious beliefs and godly virtues for peaceful conduct and relationship. In OOU, this engendered collaborative prayers for the university by christian and muslim students. In UI and UniIlorin, despite previous strained relationships, inter-religious relations between christian and muslim students has improved. Outreach programmes involve faith sharing, interaction and provision of welfare needs. They create platforms for inter-religious encounter, support and mutual understanding of each other's faiths. Ninety percent of the respondents also attested to it that outreach programmes facilitate knowledge on the import of mutual respect for religious rights, relations and tolerance, although it has caused friction due to misconception and over zealousness in times past. Social programmes (sports and excursion) are for recreation and social discourses. They facilitate appreciation, participation of students of other faiths and peaceful relationships, which break religious barriers, promotes better interaction and joint representations for mutual success. In OOU, Christian and Muslim students attend and support each other during their social programmes while MSSN UI invited Christians as facilitators. Educational programmes are for learning/tutorials, seminars and symposia for skill acquisition and development. They promote academic interactions, aid mutual quest for knowledge and advocacy against social vices. In UniIlorin, the streamlining of religious youth organisations fostered religious harmony and co-operation between christian and muslim students. Also, 90.0% of the respondents affirmed that their social and educational activities had helped to stem the tide of campus cultism and religious extremism and enhanced cordial relations among students. Scriptural studies, outreaches, social and educational activities of Christian and Muslim youth organisations have promoted inter-religious relations in the selected universities in Nigeria. These should be sustained and extended to other universities in Nigeria to further promote cordial inter-religious relations